2021
DOI: 10.1002/adma.202104249
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Simulations Reveal New Design Principles for Efficient Nanoradiosensitizers Based on Nanoscale Metal–Organic Frameworks

Abstract: photon-matter interactions, the photoelectric process is more likely to occur on high-Z elements where photoelectrons are ejected following photon absorption. Auger electrons are further generated after the holes are filled by higher-orbital electrons. In addition, inorganic nanoparticles (NPs) usually possess higher densities compared to organic molecules, leading to further enhancement of energy deposition on a per unit space basis. As a result, various studies have explored the potential of high-Z element-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 57 publications
(77 reference statements)
0
22
0
Order By: Relevance
“…For the energy range of photons considered in the current example (where the original source was 137 Cs), incoherent (Compton) scattering is a main photon-matter interaction mechanism [8][9][10][11][12][13][14][15] (see the cross-section data shown in Fig 2 ), and the dose will be delivered…”
Section: Methodology and Numerical Resultsmentioning
confidence: 99%
“…For the energy range of photons considered in the current example (where the original source was 137 Cs), incoherent (Compton) scattering is a main photon-matter interaction mechanism [8][9][10][11][12][13][14][15] (see the cross-section data shown in Fig 2 ), and the dose will be delivered…”
Section: Methodology and Numerical Resultsmentioning
confidence: 99%
“…We have recently discovered nanoscale metal–organic frameworks (nMOFs) with heavy metal secondary building units (SBUs) and photosensitizing ligands as a novel class of radiosensitizers via a unique radiotherapy‐radiodynamic therapy (RT‐RDT) mode of action [27–30] . With three‐dimensional (3D) arrays of ultrasmall heavy metal SBUs, nMOFs afford superior radiosensitization over nonporous NPs by more efficiently scattering secondary photons and electrons (Figure 1a) [31] . It was further revealed that nMOFs with larger mass attenuation coefficients exhibited stronger dose enhancement effects [31–34] …”
Section: Figurementioning
confidence: 99%
“…Ni et al reported Hf 6 -DBA and Hf 12 -DBA nMOFs (DBA = 2,5-di­( p -benzoato)­aniline) as efficient radioenhancers using the electron-dense Hf 6 O 4 (OH) 4 and Hf 12 O 8 (OH) 14 SBUs as X-ray absorbers to generate reactive oxygen species (ROS) and the open channels as well as small nMOF dimensions to facilitate ROS diffusion . The nMOFs showed a much higher radioenhancement than HfO 2 , a clinically investigated radioenhancer based on in vitro and in vivo antitumor efficacy studies as well as Monte Carlo simulations. , In 2014, Wang et al observed energy transfer from M 6 clusters to anthracene ligands in M 6 -anthracene MOFs (M = Hf and Zr) and X-ray scintillation properties of these MOFs . In 2018, Lu et al reported nMOF-mediated RT–RDT by combining X-ray absorption by Hf 12 -SBUs and photosensitizing bridging ligands. ,, The periodically arranged heavy-metal SBUs deposit X-ray energy and enhance radiolysis, leading to the RT effect, while transferring some of the absorbed energy to the photosensitizing ligands to generate singlet oxygen ( 1 O 2 ) and other ROSs, realizing the RDT effect.…”
Section: Radiotherapy–radiodynamic Therapymentioning
confidence: 99%